2017
DOI: 10.1523/eneuro.0211-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Eye Blink Rate (EBR) Is Uncorrelated with Dopamine D2 Receptor Availability and Unmodulated by Dopamine Agonism in Healthy Adults

Abstract: Spontaneous eye blink rate (EBR) has been proposed as a noninvasive, inexpensive marker of dopamine functioning. Support for a relation between EBR and dopamine function comes from observations that EBR is altered in populations with dopamine dysfunction and EBR changes under a dopaminergic manipulation. However, the evidence across the literature is inconsistent and incomplete. A direct correlation between EBR and dopamine function has so far been observed only in nonhuman animals. Given significant interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 49 publications
(62 reference statements)
0
66
1
Order By: Relevance
“…These findings are surprising in light of previous work showing how effects of cabergoline on cognitive function depend on individual baseline sEBR (Cavanagh et al, 2014) and OSPAN score (Broadway et al, 2018). However, it should be emphasized that evidence for a relationship between dopamine-proxy measures and dopamine levels is often correlational, based on studies with small sample sizes (N < 50; Cools et al, 2008), and that results are mixed (Dang et al, 2017;Sescousse et al, 2018). It is debatable whether such small-sample studies have adequate power to provide evidence for this relationship (Cremers, Wager, & Yarkoni, 2017;Rousselet & Pernet, 2012).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These findings are surprising in light of previous work showing how effects of cabergoline on cognitive function depend on individual baseline sEBR (Cavanagh et al, 2014) and OSPAN score (Broadway et al, 2018). However, it should be emphasized that evidence for a relationship between dopamine-proxy measures and dopamine levels is often correlational, based on studies with small sample sizes (N < 50; Cools et al, 2008), and that results are mixed (Dang et al, 2017;Sescousse et al, 2018). It is debatable whether such small-sample studies have adequate power to provide evidence for this relationship (Cremers, Wager, & Yarkoni, 2017;Rousselet & Pernet, 2012).…”
Section: Discussionmentioning
confidence: 68%
“…Similarly, the correlational findings we report should also be interpreted cautiously. While measures such as OSPAN and sEBR are easy to administer, the correlational evidence -as well as inconsistent findings regarding these measures (Dang et al, 2017;Jongkees & Colzato, 2016;Sescousse et al, 2018) -put pressure on their validity as an index of baseline dopamine levels.…”
Section: Discussionmentioning
confidence: 99%
“…The failure to observe an inverted-U-shaped effect in the current study might also be due to poor DA proxy measures. While the spontaneous blink rate has been extensively investigated as a proxy for DA function in animals and humans, many studies have also yielded conflicting or inconclusive results (Jongkees & Colzato, 2016;Dang et al, 2017;Sescousse et al, 2018).…”
Section: Modulation Of Da Drug Effects By Da Baselinementioning
confidence: 99%
“…However, two recent studies report opposing findings. Dang et al (2017) found no significant correlation between sEBR and D2/3-receptor availability in midbrain and striatum in humans. In addition, they observed no significant impact of bromocriptine, a dopamine agonist, on participants' sEBRs.…”
Section: Introductionmentioning
confidence: 63%